HUBUNGAN SARANA PRASARANA DI SEKOLAH DAN DI RUMAH DENGAN HASIL BELAJAR SENI RUPA SISWA KELAS X SMAN 1 LUBUK BASUNG - Ilham Muhardi, Dra. Zubaidah, M. Pd, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2014)
The purpose of this research is to analysize: 1) the corelation of fasilities or tools at the school with students’ achievement in fine art subject at tenth grade of SMA 1 Lubuk basung: 2) the corelation of fasilities or tools at home with students’ achievement in fine art subject at tenth grade of SMA 1 Lubuk basung: 3) the corelation of fasilities or tools at the school and at home with students’ achievement in fine art subject at tenth grade of SMA 1 Lubuk basung. The kind of this research is descriptive corelation. The population of this research is all of tenth grade students SMA N 1 Lubuk Basung that its number is 321 students. The technique of colecting the sample by proporsional random sampling that its nambers is 76 students. The technique of data analysis is analysis of descriptive and analysis inferential. The data that is collected will be analysized statistically by using the double corelation and SPSS program in version 16.0. Based on the result of this reseach, the researcher suggests that for all the parents at home will be able to give the fasilities at home, so will be able to help improving students achievement in fine art subject and for school, it should give the learning fasilities at school so that the students who do not have the fasilities at home will be able to use the learning fasilioties at school.Kata Kunci : Sarana Prasarana di Sekolah, Sarana Prasarana Belajar di Rumah, Hasil Belajar.